Supervision of Business Actors in Trade Through Electronic Systems According To Minister of Trade Regulation No. 31 Of 2023 - Sulistyani Eka Lestari; RM. Armaya Mangkunegara; Teguh Endi Widodo; Ruminingsih Ruminingsih; Ciptono Ciptono (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2025)
The issuance of Minister of Trade Regulation Number 31 of 2023 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Electronic Commerce is the Indonesian government's effort to regulate digital trading activities, including those conducted through social commerce platforms like TikTok Shop. This regulation aims to create a balanced trade ecosystem, ensure fair competition, and protect micro, small, and medium enterprises (MSMEs) in the midst of rapid technological advancements. However, the implementation of this regulation also raises challenges, particularly for MSME actors who rely on social commerce platforms as a marketplace. This paper aims to analyze the impact of the regulation on TikTok Shop and its implications for MSME development in Indonesia. The analysis is conducted by examining the content of the regulation and its effects on various stakeholders in the e-commerce ecosystem.